Magnetic Carbon Composite Particles for Dye Adsorption from Water and their Electrochemical Regeneration - Schneider, Michael; Ballweg, Thomas; Gross, Lennart; Cellermann, Carsten; Sanchez-Sanchez, Angela; Fierro, Vanessa; Ceizard, Alain; Mandel, Karl (Particle & Particle Systems Characterization, 2019)
Herein, the development of a novel composite particle system prepared from superparamagnetic Fe3O4@SiO2 microparticles as core and coated with a carbon shell is presented. The coating with carbon is done by pyrolyzing furan resin, which was previously deposited on the particle surface by poly-merization of furfuryl alcohol. The novel composite material thus combines magnetic and sorptive properties. Upon pyrolysis the magnetic material is converted from magnetite to α-iron and fayalite, changing its behavior from superparamagnetic to ferromagnetic with nearly zero remanence. The magnetic properties can be utilized to magnetically collect the particles dispersed in fluids, whereas the sorptive properties of the carbon shell can be used to remove organic contaminants from these fluids. The adsorption behavior of the composite particles and a potential electrochemical regeneration route are investigated, using the model dye methylene blue.
CRIS-Team Scopus Importer:2020-04-02
Keywords: carbon coating; dye adsorption; electrochemical regeneration; magnetic particles; water purification